Minimising injuries in gymnastics activities - Hume, P. (coachesinfo.com, 1999)
The initial aims of the study have been met in that a computerised data base of gymnastic injuries and their possible risk factors has been developed (and continues to be added to), and timely and appropriate medical and scientific advice upon identification of injury risk factors or injuries has been provided. Preliminary results indicate that training and musculoskeletal variables are possible risk factors for gymnastics injury. Statistical regression procedures will be used after 1 year of the study to assess any relationships between the proposed risk factors and injury occurrence and severity. It is suggested that injury data and training data continue to be collected, that risk factors be assessed and interventions developed to reduce the impact of the risk factors, that the effectiveness of the interventions be evaluated, and that clear and frequent communication with all parties is essential. Although data collection can be somewhat laborious and time consuming, the results do provide coaches and athletes with subjective data to assess the training program and the impact on the gymnasts' musculoskeletal growth and general health.